2017
DOI: 10.1167/iovs.16-21305
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Binocular Fixation Affects Reaction Times But Not Implicit Motor Learning in Dyslexia

Abstract: Unstable binocularity in dyslexia may affect RTs but was not related to poor IML skills. Impaired IML in dyslexia was independent of the viewing conditions (monocular versus binocular) and may be related to cerebellar deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This, in turn, could be reflected by low adaptation rate and inability to fully reduce fixation disparity. The idea that the cerebellum may be involved in controlling VPA and other oculomotor deficits was also suggested in other studies which demonstrated impaired ability of implicit motor learning (one of the fundamental cerebellar functions) in subjects with binocular problems [56] and dyslexia [40], poor body balance control in adults [57] and children [58] with strabismus or changes in walking strategies applied by patients with strabismus [59]. All of these functions depend, at least to some extent, on cerebellar control.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This, in turn, could be reflected by low adaptation rate and inability to fully reduce fixation disparity. The idea that the cerebellum may be involved in controlling VPA and other oculomotor deficits was also suggested in other studies which demonstrated impaired ability of implicit motor learning (one of the fundamental cerebellar functions) in subjects with binocular problems [56] and dyslexia [40], poor body balance control in adults [57] and children [58] with strabismus or changes in walking strategies applied by patients with strabismus [59]. All of these functions depend, at least to some extent, on cerebellar control.…”
Section: Discussionmentioning
confidence: 91%
“…However, in case of binocular disorders, the slow vergence system is not able to maintain a proper vergence posture and reduce FD, causing strain of the fast controller, which leads to visual symptoms during sustained viewing. It suggests that sustained FD, often observed in subjects with decompensated phoria [1, 38, 39] or individuals with reading problems [40, 41], might be treated as an indicator of impaired VPA. FD was not measured in the present study but in future studies it would be interesting to evaluate the correlation between FD and VPA skills in subjects with symptomatic heterophoria, dyslexia and patients with neurological (cerebellar) disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies support the suggestion that cerebellar dysfunctions are commonly observed in developmental dyslexia (Eckert, Leonard, Richards, Aylward, Thomson, & Berninger, 2003;Nicolson, Fawcett, & Dean, 2001;Stoodley, Fawcett, Nicolson, & Stein, 2005;Vicari, Finzi, Menghini, Marotta, Baldi, & Petrosini, 2005;Vicari, Marotta, Menghini, Molinari, & Petrosini, 2003). Several investigations have reported dyslexic readers with deficits in vergence and other oculomotor function (Bucci, Brémond-Gignac, & Kapoula, 2008;Bucci, Nassibi, Gérard, Bui-Quoc, & Seassau, 2012;Kapoula & Bucci, 2007;Legrand, Bui-Quoc, Doré-Mazars, Lemoine, Gérard, & Bucci, 2012;Przekoracka-Krawczyk, Brenk-Krakowska, Nawrot, Rusiak, & Naskręcki, 2017). In addition, studies on strabismic patients also suggest dysfunction in the cerebellum (Gaertner, Creux, Espinasse-Berrod, Orssaud, Dufier, & Kapoula, 2013;Przekoracka-Krawczyk, Nawrot, Kopyciuk, & Naskrȩcki, 2015).…”
Section: Researchers Have Developed Several Paradigms Tomentioning
confidence: 82%
“…When comparing the performance on SL tasks in a group of participants with developmental dyslexia (DD) to a control group (TD), the findings on the relationship between SL and reading outcome were mixed. While some studies found a significant group difference (e.g., Lukasova et al, 2016; Przekoracka-Krawczyk et al, 2017), others did not (e.g., Inácio et al, 2018; Staels & Van den Broeck, 2017). These inconsistent findings motivated the present meta-analysis, where we sought to symmetrically examine the magnitude of the association between SL and language and between SL and reading.…”
Section: The Link Between Sl and Language Developmentmentioning
confidence: 97%